2018
DOI: 10.1016/j.diii.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Tomosynthesis in musculoskeletal pathology

Abstract: Tomosynthesis is an imaging technique that uses standard X-ray equipment with digital flat panel detectors to create tomographic images from very low-dose projections obtained at different angles. These images are parallel to the plane of the detector. Filtered back-projection or iterative reconstruction algorithms can be used to produce them. Iterative reconstruction used with a metal artifact reduction algorithm reduces metal artifacts, and therefore, improve image quality and in-depth spatial resolution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…DTS is widely used in various imaging fields owing to its high in-plane resolution. For musculoskeletal studies, DTS is useful for analyzing high-contrast structures such as the bones [ 12 ]. DTS is superior to radiography for visualizing superimposed anatomical structures because multiple images from various angles are taken while the X-ray tube is swept within a specified range [ 17 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTS is widely used in various imaging fields owing to its high in-plane resolution. For musculoskeletal studies, DTS is useful for analyzing high-contrast structures such as the bones [ 12 ]. DTS is superior to radiography for visualizing superimposed anatomical structures because multiple images from various angles are taken while the X-ray tube is swept within a specified range [ 17 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digital tomosynthesis (DTS) is a recently developed imaging modality that uses standard X-ray equipment with digital flat panel detectors to create images from a series of projection radiographs obtained at different angles [ 10 11 12 ]. It has been shown to be useful for imaging various body parts, including the breast [ 13 14 ], chest [ 15 ], head and neck [ 16 ], and musculoskeletal system [ 17 18 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tomosynthesis offers the advantage of being performed at the same time as standard radiography, and it offers greater precision in the detection of bone anomalies. 4,[29][30][31]…”
Section: Standard Radiographymentioning
confidence: 99%
“…It is currently being used in routine clinical practice for imaging of the chest and breast, and it is beginning to be used for bone healing. [1][2][3][4][5] Ha et al 2 reported that tomosynthesis provided superior diagnostic information compared with other imaging methods during the postoperative evaluation of wrist fractures. Simoni et al 6 also reported that tomosynthesis and computed tomography (CT) detected a similar number of erosions in patients with rheumatic arthritis.…”
mentioning
confidence: 99%
“…Tomosynthesis is starting to attract attention from those who perform musculoskeletal diagnosis. 1,[7][8][9][10] Anterior cruciate ligament (ACL) reconstruction frequently is used to treat athletes and young patients who experience ligament injury. Although various grafts are considered for ACL reconstruction, the hamstring tendon or boneepatellar tendonebone (BPTB) graft is mainly used for the procedure.…”
mentioning
confidence: 99%